P17 Effect of interventional stent treatment of native and recurrent coarctation of aorta on blood pressure. (2nd March 2016) - Kasem, M; Gargani, Y; Bentham, J; Ballard, G; Thomson, JD
Abstract : Aim/Background: The aim of this study was to describe the clinical impact of management of coarctation of the aorta by transcatheter stent placement in the context of longer term management of systemic hypertension. In the long term, poor outlook associated with untreated coarctation of the aorta is likely to relate to uncontrolled systemic hypertension. Transcatheter stent placement to treat native and recurrent coarctation of the aorta is an established therapy in adolescents and adults. There remains confusion about longer term outcomes, particularly the relation between procedural success and improvement in blood pressure (BP) control. Improvement in lifelong systemic BP control after transcatheter stent placement remains unproved. Results: 89 patients underwent transcatheter stent placement over a 14-year period (2001 to 2015) at the Yorkshire Heart Centre. The average age at the time of procedure was 29.3 years (range 6 to 59). Figure 1 shows the ages of the patients undergoing treatment divided into 3 age groups. Figure 2 demonstrates that native coarctations formed the majority of the cases seen, followed by recurrent coarctations, and it shows that only a minority were as part of complex congenital heart disease. We found there was a reduction in peak systolic gradient across the narrowed segment from mean of 27.7 to <5 mm Hg in 84 patients. Figure 3 shows the differences in peak systolic gradient before and after intervention. After stent placement, there was a significant improvement in systolic BP control at early and later follow-up (mean 156.2 mmHg before the procedure and 129.6 mmHg at 3.51-year follow-up, p < 0.0001), as shown in Figure 4 .  Conclusion: Transcatheter stent placement for the management of aortic coarctation is associated with a reduction in systolic BP that is maintained over the medium term. A significant minority of patients remain significantly hypertensive, and the best management strategy for this group of patients remains unclear.